2013
DOI: 10.1155/2013/474963
|View full text |Cite
|
Sign up to set email alerts
|

Association between Inflammatory Marker, Environmental Lead Exposure, and Glutathione S-Transferase Gene

Abstract: A number of studies suggested that lead is related to the induction of oxidative stress, and alteration of immune response. In addition, modifying these toxic effects varied partly by GST polymorphism. The objectives of this study were to assess the association between the lead-induced alteration in serum hs-CRP, with GSTM1, GSTT1, and GSTP1 Val105Ile genetic variations and the health consequence from environmental lead exposure. The 924 blood samples were analyzed for blood lead, CRP, and genotyping of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…Unequivocal results were obtained within the Electric Generating Authority of Thailand (EGAT 2) programme 21. The examined population of men environmentally exposed to Pb (n=924) was divided into quartiles based on the average Pb concentration in the blood (24.4; 39.5; 57.7; 92.1 µg/L).…”
Section: Discussionmentioning
confidence: 99%
“…Unequivocal results were obtained within the Electric Generating Authority of Thailand (EGAT 2) programme 21. The examined population of men environmentally exposed to Pb (n=924) was divided into quartiles based on the average Pb concentration in the blood (24.4; 39.5; 57.7; 92.1 µg/L).…”
Section: Discussionmentioning
confidence: 99%
“…Participants with GSTT1 null polymorphism had higher Pb in blood when compared to those that expressed the enzyme. A recent study carried out by Sirivarasai et al (2013) showed that polymorphisms in GSTM1, GSTT1, as well as double deletion of GSTM1/GSTT1 altered inflammatory parameters in Thai subjects exposed to Pb (levels ranged from 6.5 to 25 mg/dL). Here, we did not observed effects of GSTM1/GSTT1 double deletion on either Hg or Pb concentrations.…”
Section: Hg In Blood Amentioning
confidence: 99%
“…Glutathione-s-transferase Pi1(GSTP1) has been shown to reduce the effects of oxidative stress through free radical clearance (Hayes and Strange, 2000), and may modify the relationship between lead and cognitive function in the elderly (Eum et al, 2013) and inflammatory markers in adult males (Sirivarasai et al, 2013). Finally, the gene TfC2 encodes the transferrin protein that is responsible for iron transport, and interacts with HFE (Namekata et al, 1997).…”
Section: Introductionmentioning
confidence: 99%